Cardioprotection by Conditioning Mimetic Drugs - Santillo, Elpidio; Migale, Monica; Postacchini, Demetrio; Balestrini, Fabrizio; Antonelli Incalzi, Raffaele (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2016)
Background: At present, ischemic heart disease (IHD) is one of the main causes of morbidity and mortality world-wide. An important insight into both IHD pathophysiology and cardioprotection was achieved in 1986 when Murry et al. described for the first time the ischemic preconditioning (IP). IP can be defined as an innate phenomenon by which brief episodes of ischemia confer protection to a tissue from a subsequent more protracted ischemic insult. Suggested mechanisms explaining IP comprise the action of circulating substances (e.g. adenosine, bradykinin, nitric oxide). These mediators are released after a prolonged ischemic stress, causing activation of molecular pathways that induce favorable posttranslational changes of proteins and adaptive modifications in genetic expression. Purpose: Briefly review evidences from clinical studies on drugs that exert their effects by mimicking IP, discussing their therapeutic properties and the potential clinical employment in order to obtain cardioprotection. Methods: Literature regarding IP mimicking pharmacological agents was searched in Medline and Google Scholar. Authors reviewed relevant researches in English language including both clinical studies and reviews of clinical studies published from 1986 to 2016. Results: Several pharmacological agents reproducing IP protective actions have been evaluated in many clinical trials. Examined molecules include adenosine, nicorandil and atrial natriuretic peptide. Interestingly IP mimicking effects of drugs have been also analyzed perioperatively in the context of ischaemia-reperfusion heart injury. Moreover evidences suggest that also some anaesthetic drugs (especially volatile agents) are able to provide myocardial protection by inducing IP. Conclusion: Drugs capable of mimicking IP exhibit a high therapeutic potential because of their properties of eliciting an effective cardioprotective signaling. Future studies should clarify the optimal doses and timing of administration of IP mimetic agents in order to favor the advent of new cardioprotective strategies beyond available reperfusive therapies.
Keywords: ischemia/reperfusion injury